2017
DOI: 10.1177/2472555217717639
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Culture Filtrate of Prevalent Mycobacterium tuberculosis Strains: 2D-PAGE Map and MALDI-TOF/MS Analysis

Abstract: Although diverse efforts have been done to identify biomarkers for control of tuberculosis using laboratory strain Mycobacterium tuberculosis H37Rv, the disease still poses a threat to mankind. There are many emerging M. tuberculosis strains, and proteomic profiling of these strains might be important to find out potential targets for diagnosis and/or prevention of tuberculosis. We evaluated the comparative proteomic profiling of culture filtrate (CF) proteins from prevalent M. tuberculosis strains (Central As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Expression proteomics {2-dimensional gel electrophoresis (2-DE)} coupled with MALDI-TOF-MS and bioinformatic tools has emerged as a direct approach for the separation, identification and characterization of proteins which could be used to find out potential drug targets and diagnosis of resistance as well as pathogenesis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Since the last decade, a panel of discovery (expression), targeted proteomics and bioinformatics-based studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] have been accumulated on M. tuberculosis pathogenesis and drug resistance which showed differential expression of a panel of known and unknown proteins and suggested that these proteins might be used in diagnostics and as drug targets against drug resistant TB. We have previously reported that Rv0148 (hypothetical protein/putative short-chain type dehydrogenase/reductase) was overexpressed in aminoglycosides-resistant M. tuberculosis .…”
Section: Proteomics and Bioinformatics Explored Potential Drug Tarmentioning
confidence: 99%
“…Expression proteomics {2-dimensional gel electrophoresis (2-DE)} coupled with MALDI-TOF-MS and bioinformatic tools has emerged as a direct approach for the separation, identification and characterization of proteins which could be used to find out potential drug targets and diagnosis of resistance as well as pathogenesis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Since the last decade, a panel of discovery (expression), targeted proteomics and bioinformatics-based studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] have been accumulated on M. tuberculosis pathogenesis and drug resistance which showed differential expression of a panel of known and unknown proteins and suggested that these proteins might be used in diagnostics and as drug targets against drug resistant TB. We have previously reported that Rv0148 (hypothetical protein/putative short-chain type dehydrogenase/reductase) was overexpressed in aminoglycosides-resistant M. tuberculosis .…”
Section: Proteomics and Bioinformatics Explored Potential Drug Tarmentioning
confidence: 99%
“…Ultimately, IPG strip was detached and enclose it on to second dimension electrophoresis. The second dimension was achieved on 10% gel electrophoresis for 1 h and then gels (proteins) were stained with Coomassie Brilliant Blue as described previously 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Besides an AFB smear (Auramine O method), the homogenized sputum was used to evaluate recovery efficiency and decontamination rate (NaOH-NALC vs. PU methods). Mycobacterial culture was performed using an MGIT 960 (Becton Dickinson, Franklin Lakes, NJ, USA), and the mycobacterial strains were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS; Bruker Daltonics, Bremen, Germany) [ 17 ] or 16S rRNA gene sequencing [ 18 ].…”
Section: Methodsmentioning
confidence: 99%